Restoration of anterior esthetics with Richmond crown - Faisal Khan; Sunil Kumar Mishra (BLDE University Journal of Health Sciences, 2017)
Conservation of natural tooth is the main focus of the present era of dentistry, and endodontist and prosthodontist play a major role in conserving and restoring tooth function and esthetics. Restoring grossly destructed endodontically treated teeth is a challenge in restorative dentistry. Restoring such compromised teeth often requires additional support from the root canal with the help of post and core restoration. This case report describes a patient with grossly decayed central incisor and reduced interocclusal space treated with Richmond crown.